2017
DOI: 10.1080/1554480x.2017.1376671
|View full text |Cite
|
Sign up to set email alerts
|

Not a stale metaphor: the continued relevance of pedagogical content knowledge for science research and education

Abstract: Pedagogical content knowledge (PCK) is a foundation for teacher standards such as the Interstate Teacher Assessment and Support Consortium (InTASC) (Council of Chief State School Officers, 2011) and a critical element of teacher preparation and professional development for multiple fields, including science teaching (Purzer, Moore, Baker, & Berland, 2014). But several years ago Settlage (2013) presented a powerful critique of PCK, rejecting the way it positions knowledge in the abstract, "solely … what teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Studies have shown that students' misconceptions are topic specific and elicited by the context of instruction (Chen et al, 2016;Auerbach et al, 2018). Likewise, teachers' PCK, or KOSM, is also considered to be topic or domain specific (Blömeke et al, 2015), situated in varying contexts (Ball et al, 2008;Lee and Luft, 2008;Borowski et al, 2010;Depaepe et al, 2013;Gess-Newsome, 2015;Hayden and Eades Baird, 2018). Depaepe et al (2015) showed that students had lower scores on items that required a higher level of PCK of their teachers, compared with items that required only teachers' SMK.…”
Section: Misconception Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that students' misconceptions are topic specific and elicited by the context of instruction (Chen et al, 2016;Auerbach et al, 2018). Likewise, teachers' PCK, or KOSM, is also considered to be topic or domain specific (Blömeke et al, 2015), situated in varying contexts (Ball et al, 2008;Lee and Luft, 2008;Borowski et al, 2010;Depaepe et al, 2013;Gess-Newsome, 2015;Hayden and Eades Baird, 2018). Depaepe et al (2015) showed that students had lower scores on items that required a higher level of PCK of their teachers, compared with items that required only teachers' SMK.…”
Section: Misconception Strengthmentioning
confidence: 99%
“…, 2010 ; Depaepe et al. , 2013 ; Gess-Newsome, 2015 ; Hayden and Eades Baird, 2018 ). Depaepe et al.…”
Section: Introductionmentioning
confidence: 99%
“…Our claim is that more research as well as research-based development of games for pre-service teachers is needed. Therefore, we set out to develop a game for higher education that meets the above-mentioned quality criteria and can be flexibly implemented into the framework of learning about misconceptions and therefore develop pre-service teachers' PCK [25,26]. Misconceptions have been one of the most prominent, but also one of the most complex, topics in science education research and thus also in science teacher training for almost 50 years [27].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Since then, PCK has been used extensively as a construct to research teacher cognition as well as a framework to model practice (Abell, 2008; Berry & van Driel, 2012; Goodnough, 2006; Magnusson et al, 1999). However, Hayden and Baird (2017) point out that while there is extensive literature that describes PCK, its use and assessment among prospective and practicing teachers, more illustrations of what PCK is and how practitioners make sense of this construct are needed.…”
Section: Introductionmentioning
confidence: 99%